KEANEKARAGAMAN DAN POLA SEBARAN FAMILI ARACEAE DI HUTAN DESA BUKUM KECAMATAN SIBOLANGIT KABUPATEN DELI SERDANG SUMATERA UTARA - Diana, Rahma; Hutasuhut, Melfa Aisyah; Idami, Zahratul (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2022)
The family Araceae, the taro family, has a terrestrial habitus, for better or for worse, submerged or submerged in water. Araceae is also very abundant and diverse in wet tropical areas such as the Bukum Village Forest area. This study aims to determine the types of the Araceae family, the diversity index and the distribution pattern of the Araceae family in the Forest of Bukum Village, Sibolangit District, Deli Serdang Regency, North Sumatra which was carried out in December 2021 - February 2022. The method used was exploratory with the technique of making square plots. by purposive sampling on 2 transects, each of which has 8 plots of observations. The results of the study were 24 species from the Araceae family with the most common species being Schismatoglottis calyptrata (Roxb) with 157 individuals. There are at least 4 species of individuals, namely Aglaonema commutatum Schott, Aglaonema nebulosum N.E.Br., Homalomena rostrata Griff. and Syngonium podophyllum Schott by 2 individuals. The diversity index of transect I was 2.00 and transect II was 2.36. The diversity index data shows moderate environmental diversity, because the productivity is quite high, the ecosystem condition is balanced and the ecological pressure is moderate. The morisita index on transect I of 1.59 shows the pattern of distribution is moderate, this occurs due to uneven (uniform) abiotic conditions although in a narrow location. The morisita index on transect II of 0.98 indicates an even distribution pattern, due to individual competition which encourages the distribution of space evenly.